Lessons in laughter : the autobiography of a deaf actor - Bragg, Bernard, 1928-; Bergman, Eugene (Washington, D.C. : Gallaudet University Press, 1989)
The story of Bernard Bragg and his astonishing lifelong achievements in the performing arts.
Keywords: Bragg, Bernard, -- 1928-; National Theatre of the Deaf; Actors -- United States -- Biography; Deaf -- United States -- Biography; Authors, American -- 20th century -- Biography